Altered Pattern of Immunoglobulin A-Targeted Microbiota in Inflammatory Bowel Disease After Fecal Transplantation - Huang, Wen-qi; Huang, Hong-Li; Peng, Wu; Liu, Yan-Di; Zhou, You-Lian; Xu, Hao-Ming; Zhang, Liang-jie; Zhao, Chong; Nie, Yu-Qiang (Frontiers in Microbiology, 2022)
Adaptive immune response to the gut microbiota is one of the main drivers of inflammatory bowel disease (IBD). Under inflammatory conditions, immunoglobulin (Ig)-targeted bacteria are altered. However, changes in Ig-targeted bacteria in Asian patients with IBD with ulcerative colitis (UC) remain unclear. Furthermore, changes in IgA-targeted bacteria in patients with UC treated with fecal microbiota transplantation (FMT) are unclear. Here, we analyzed fecal samples of patients with IBD and patients with UC before and after FMT by flow cytometry. We found that the percentage of IgA/G-coated bacteria can be used to assess the severity of IBD. Besides oral pharyngeal bacteria such as Streptococcus, we hypothesized that Megamonas, Acinetobacter, and, especially, Staphylococcus might play an important role in IBD pathogenesis. Moreover, we evaluated the influence of FMT on IgA-coated bacteria in patients with UC. We found that IgA-bacterial interactions were re-established in human FMT recipients and resembled those in the healthy fecal donors. Additionally, the IgA targeting was not influenced by delivery methods: gastroscopy spraying and colonic transendoscopic enteral tubing (TET). Then, we established an acute dextran sulfate sodium (DSS)-induced mouse model to explore whether FMT intervention would impact IgA/G memory B cell in the intestine. We found that after FMT, both IgA/G memory B cell and the percentage of IgA/G-targeted bacteria were restored to normal levels in DSS mice.